Is there evidence for an association between changes in training load and running-related injuries? A systematic review - Damsted, C.; Glad, S.; Oestergaard Nielsen, R.; Sorensen, H.; Malisoux, L. (International Journal of Sports Physical Therapy, 2018)
Background: Sudden changes (increases and decreases) in training load have been suggested to play a key role in the development of running-related injuries. However, the compiled evidence for an association between change in training load and running-related injury does not exist.